Metabolite profiling of Artemisia carvifolia Buch transgenic plants and estimation of their anticancer and antidiabetic potential. (March 2020) - Dilshad, Erum; Ismail, Hammad; Khan, Mubarak Ali; Cusido, Rosa Maria; Mirza, Bushra
Abstract: Diabetes and cancer are common diseases worldwide with terrific effect on human health. In the present study, a high valued medicinal plant Artemisia carvifolia Buch was subjected for evaluation of anticancer and antidiabetic potential. Previously produced rol B and rol C gene transgenic plants of A. carvifolia were also compared with the wild type plant for a differential count of cytotoxicity and antidiabetic activity. Lowest IC50 values were shown by rolB transgenic line TB4 for alpha-glucosidase (838.6  μg/ml), alpha-amylase (742.8  μg/ml) and dipeptidyl peptidase-4 (1300 μg/ml) in contrast to the wild type plant which showed IC50 values of 1608.4 μg/ml for alpha-glucosidase, 1973.8 μg/ml for alpha-amylase and 1800 μg/ml for dipeptidyl peptidase-4. Among rolC transgenic plants, TC1 showed lowest IC50 value i.e. 873 μg/ml for alpha-glucosidase, 747.7 μg/ml for alpha-amylase and 1400 μ/ml for dipeptidyl peptidase-4. Viability of the cancer cells including HeLA, HePG2 and MCF7 decreased to 80% when treated with methanolic extract of the plant and it decreased to 70% when treated with n-hexane extract. Cytotoxic effect was found more enhanced when cells were treated with both the extracts combined, showing synergism between flavonoids and artemisinin. Rol B transformants showed slightly better activity than the rol C transformants which were found superior in activity than the wild type plant. Metabolite profiling by ESI/MS-TOF showed the involvement of significant plant secondary compounds in antidiabetic and anticancer potential in the extracts of transgenic lines. Vital amino acids, substantial phenylpropanoids and important phytochemicals were detected at a higher level in rol B and rol C transgenic plants than wild type plants.